Efficacy of the organic Ecotensor SYS adjuvant, in the control of black Sigatoka (Mycosphaerella fijiensis) in plantain cultivation (Musa AAB simmonds) (Revista Sistemas de Producción Agroecológicos, 2021)
A study was carried out whose purpose was to determine the efficacy of the organic adjuvant (Ecotensor SYS) in mixture with a fungicide for agricultural use, establishing doses for recommendation and evaluating possible effects of phytotoxicity of Ecotensor in banana plants (Musa AAB Simmonds); test carried out for the control of Mycosphaerella fijiensis in plantain cultivation (Musa AAB Simmonds). The tests were carried out in open field in experimental plots of the crop, in the department of Meta, in the municipalities of Granada and Fuente de Oro, each plot had an area of ​​250 m2 with an average of 10 meters wide by 25 meters long, the total area was 1000 m2, for each trial. A completely randomized experimental design was carried out. The results show that the fungicide applications with Ecotensor provide a better level of disease control compared to the fungicide treatments with hypotensor and fungicide without adjuvant. The application of SYS Ecotensor did not generate damage or symptoms of phytotoxicity on the foliage of banana plants (Musa AAB Simmonds). Therefore, it is concluded that favorable advantages are obtained when using fungicide accompanied by the evaluated organic adjuvant Ecotensor, and that the dose for application recommendation is 1,0 ml/l of wáter.
Keywords: phytotoxicity; fungicide; disease; degree of severity